2022
DOI: 10.3389/fendo.2022.920482
|View full text |Cite
|
Sign up to set email alerts
|

Expert Opinion on the Management of Growth Hormone Deficiency in Brain Tumor Survivors: Results From an Italian Survey

Abstract: BackgroundGrowth hormone deficiency (GHD) is the first and most common endocrine complication in pediatric brain tumor survivors (BTS). GHD can occur due to the presence of the tumor itself, surgery, or cranial radiotherapy (CRT).AimsThis study aimed to evaluate management and adherence to current guidelines of the Italian centers engaged in the diagnosis and follow-up of GHD patients with BTS.MethodsA multidisciplinary scientific board of pediatric endocrinologists, oncologists and radiologists with neuroimag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…GH can lead to significant metabolic changes by increasing cholesterol and interfering with renin angiotensin ( 38 ). Although there is no definite evidence about carcinogenesis of GH in therapeutic dose, the safety of long-term drug use in patients with malignant tumor, aggravating metabolic disorder, and other unforeseen adverse events should be continuously monitored ( 39 , 40 ). It has not been found that the application of GH in IVF treatment will cause adverse effects on hysteromyoma, endometriosis, adenomyosis, adverse pregnancy outcomes, etc., but long-term follow-up and observation are still needed.…”
Section: Safety Of Gh Treatmentmentioning
confidence: 99%
“…GH can lead to significant metabolic changes by increasing cholesterol and interfering with renin angiotensin ( 38 ). Although there is no definite evidence about carcinogenesis of GH in therapeutic dose, the safety of long-term drug use in patients with malignant tumor, aggravating metabolic disorder, and other unforeseen adverse events should be continuously monitored ( 39 , 40 ). It has not been found that the application of GH in IVF treatment will cause adverse effects on hysteromyoma, endometriosis, adenomyosis, adverse pregnancy outcomes, etc., but long-term follow-up and observation are still needed.…”
Section: Safety Of Gh Treatmentmentioning
confidence: 99%
“…During the last few decades, the pediatric brain cancer survival rate increased due to the improvement in therapeutic regimens, which involve the combination of chemotherapy, radiotherapy, and supportive therapies (e.g., high dosage steroids, antibiotics, and growth factors) [1,2]. These treatments, although they facilitate recovery from cancer, have longterm toxic effects on organs and systems like the kidneys, heart, hearing, and endocrine system [3][4][5][6][7][8]. Furthermore, they also cause the activation of chronic inflammatory processes and metabolic alterations, which can facilitate the onset of metabolic syndrome and increase cardiovascular risk [9].…”
Section: Introductionmentioning
confidence: 99%